Evidence of robust participation by an equatorial 4-O group in glycosylation on a 2-azido-2-deoxy-glucopyranosyl donor. Issue 20 (27th February 2017) - Yao, Dongming; Liu, Yichu; Yan, Shiqiang; Li, Yingxia; Hu, Chun; Ding, Ning
Abstract : An isolated bridging intermediate as evidence of equatorial 4- O group participation in glycosylation. Abstract : Although there are numerous claims of remote group participation leading to the synthesis of the expected glycosides with improved anomeric geometry outcome in glycosylation, there is still a lack of enough strong evidence and this has led to a long-term debate, particularly for equatorial 4- O group participation. In this work, we were able to synthesize and isolate a stable seven-membered trichlorooxazepine ring bridging intermediate with a high yield by employing a 2-azido-2-deoxy-glucopyranosyl donor, which provides strong evidence to support the putative participation of the equatorial 4- O group in glycosylation.